Keroncong Music Reflects the Identity of Indonesia - Alfian, Magdalia (TAWARIKH, 2013)
ABSTRACT: During the course of its history, âkeroncongâ which is an Indonesian music was popular during the 1970s and 1980s. However, in its development, âkeroncongâ music has changed and it gradually reflected the personality of Indonesia. But, the development of information technology in 1990s has an impact on the âkeroncongâ music and since it has made the âkeroncongâ less popular. There are some preservations towards the âkeroncongâ music. One of them is the effort from the young generation in performing âkeroncongâ music, which is by incorporating elements from other musical genres such as âRockâ, âJazzâ, and âDangdutâ (Malay orchestra music), so new terms of âCong-Rockâ, âCong-Jezzâ, and âCong-Dutâ began to appear. Finally, âkeroncongâ music, which is much older than the Republic of Indonesia (1945), has actually contributed to and an active role in the struggle for Indonesian independence and has also been translated into various international languages. âKeroncongâ music has grown and evolved, showing the identity and personality of the Indonesian nation. That way, it is not an exaggeration if âkeroncongâ is proposed as a World Heritage.KEY WORDS: âKeroncongâ music, popular art, development and preservation, andÂ  Indonesian personality.About the Author: Dr. Magdalia Alfian is a Senior Lecturer at the Department of History, Faculty of Humanities UI (University of Indonesia), UI Campus, Depok, West Java, Indonesia. She can be contacted via her e-mail address at: magdalia_alf10@yahoo.comHow to cite this article? Alfian, Magdalia. (2013). âKeroncong Music Reflects the Identity of Indonesiaâ in TAWARIKH: International Journal for Historical Studies, Vol.4(2) April, pp.171-186. Bandung, Indonesia: ASPENSI [Asosiasi Sarjana Pendidikan Sejarah Indonesia] and UVRI [Universitas Veteran Republik Indonesia], ISSN 2085-0980. Chronicle of the article: Accepted (February 22, 2013); Revised (March 25, 2013); and Published (April 28, 2013).